The Board for International Broadcasting, Radio Free Europe and Radio Liberty : hearings before the Committee on Foreign Affairs, House of representatives . ninety-third congress, second session on H. R. 14780 ; May 14 and 15, 1974 (U. S. Government Printing Office, 1974)
Donation of Edward A. Corcoran.